The Importance of Cross-border Cooperation on Regional Development: Evidence from the Euroregion, Neisse - Zdražil, Pavel; Kozuń-Cieślak, Grażyna (Univerzita Pardubice, 2016)
This paper aims to focus on the importance of cross-border cooperation in respect of regional development. We aim to examine whether the regions of the euroregion, Neisse, experience different patterns of development in economic performance compared against both the neighbouring regions in their country, and to their country itself. The methodological framework is based on correlation analysis of volumes, where the non-stationary issue has been examined via the ADF unit root test. The results showed that the initiatives of the cross-border cooperation appear to be vital instruments of the European Union cohesion policy in the case of the euroregion, Neisse, but at the same time, are very ambiguous as well. The Czech and Polish regions of Neisse seem to be influenced by the ‘cross-border cooperation factor’, since they differ from the benchmark entities; however, no obvious differences have been found to occur on the German side of the border. Furthermore, the figures obtained show that the growth rates of the Czech and Polish regions of Neisse were slower than in their neighbouring regions and respective countries. In summary, we may suggest that some linkages within the euroregion, Neisse, do exist, but we may ask whether their existence is unfavourable or whether their potential is or is not used in the best way possible.
Význam přeshraniční spolupráce pro regionální rozvoj: příklad euroregionu Nisa
Keywords: cross-border cooperation; Neisse; cohesion; euroregions; regional development; přeshraniční spolupráce; Nisa; koheze; euroregiony; regionální rozvoj